Digital Public Reporting Systems for Evaluating Health Care Quality : Systematic Review - Du, Lanmei; Suomi, Reima; Damalie, Elorm (Canada, 2026)
Background
Health care public reporting (PR) refers to making information about the quality and performance of health care providers available to the public. The primary targeted use of PR is the selection of a health care provider. Previous studies suggest that PR has improved health care quality; however, the overall adoption rate of PR systems remains low. Misalignment between PR information and users’ actual needs can explain this gap.
Objective
This study conducts a systematic literature review of PR systems in health care, aiming to explore how data encoding and presentation influence user utilization, with particular attention to the impact of data inconsistencies and inaccuracies on actual use.
Methods
A literature search was conducted on 5 electronic databases (Web of Science, CINAHL, Embase, PsycINFO, and PubMed), focusing on studies providing information in health care from an individual perspective. Subsequently, the quality of the included studies was assessed using the Mixed Methods Appraisal Tool (McGill University). Finally, a total of 25 empirical studies were included in this study.
Results
Among the 25 studies, 40% (10/25) investigated website presentation formats, 20% (5/25) explored dashboard-based data presentation formats in PR systems, 48% (12/25) examined data quality, and 20% (5/25) addressed user heterogeneity. Quantitative methods were used in 80% (20/25) of studies, while qualitative and mixed method designs accounted for 16% (4/25) and 4% (1/25), respectively. Findings suggest that standardized website and dashboard guidelines improve data reliability and user comprehension and that user heterogeneity mediates the effects of structural and process indicators on outcomes. Data collection was completed in February 2025, and the study was projected to be fully completed by September 2025.
Conclusions
This study provides an integrated structure-process-outcome–based framework for PR in health care. By presenting data through dashboards, inconsistencies and inaccuracies in data across different web pages can be mitigated, thereby decreasing conflicting information and improving comprehension in PR systems. Based on the literature findings and identified knowledge gaps, this study also proposes future research directions for online PR.